FAKTOR RISIKO YANG BERPENGARUH TERHADAP KEJADIAN MYOPIA PADA REMAJA DI SEMARANG - Sri Suparti; Sri Martunjung Purusatama; Machbub Junaidi (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Teenager very need some information, 80 %of informations from the vision,if there are abnormality visions so make disturbed of activites.and the abnormality is called myopia.Myopia make decrease of the vision. Teenager that have many activities have myopia. The research is to know about the risk factor that make myopia,some of them are using handpohone,health statue,distance of reading,and sport. Methode of this research is observational with cross sectional study,with eighty three of samples. there are 83 respondences. The research instrument consisted of the Trial Lens, Trial Frame, Optotype and Pupil Distance use bivariat multivariat date analyze use spss programe. Varibles this research that make myopia are gender (p:0,013 OR 0,135 95% CI 0.028-0.661), using handphone value (p:0,015 OR 3,839 95% CI =1,295-11,377). Varibles that influence the incidence of myopia are gender, using handphone more than three hours every day. Distance of reading,nutrition status and sport not influential of myopia of gender.Key: Myopia,teenager,risk factor